Physicians’ Attitudes Towards Copy and Pasting in Electronic Note Writing - O’Donnell, Heather C. (Springer-Verlag, 2008)
BACKGROUND: The ability to copy and paste text within computerized physician documentation facilitates electronic note writing, but may affect the quality of physician notes and patient care. Little is known about physicians’ collective experience with the copy and paste function (CPF). OBJECTIVES: To determine physicians’ CPF use, perceptions of its impact on notes and patient care, and opinions regarding its future use. DESIGN: Cross-sectional survey. PARTICIPANTS: Resident and faculty physicians within two affiliated academic medical centers currently using a computerized documentation system. MEASUREMENTS: Responses on a self-administered survey. RESULTS: A total of 315 (70%) of 451 eligible physicians responded to the survey. Of the 253 (80%) physicians who wrote inpatient notes electronically, 226 (90%) used CPF, and 177 (70%) used it almost always or most of the time when writing daily progress notes. While noting that inconsistencies (71%) and outdated information (71%) were more common in notes containing copy and pasted text, few physicians felt that CPF had a negative impact on patient documentation (19%) or led to mistakes in patient care (24%). The majority of physicians (80%) wanted to continue to use CPF. CONCLUSIONS: Although recognizing deficits in notes written using CPF, the majority of physicians used CPF to write notes and did not perceive an overall negative impact on physician documentation or patient care. Further studies of the effects of electronic note writing on the quality and safety of patient care are required. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-008-0843-2) contains supplementary material, which is available to authorized users.